Living Islam in the Sinandong Oral Tradition: A Study of the Malay Society in Tanjungbalai - Asriani Matondang; Hasnah Nasution (Hikmah, 2026)
This study aims to explore the values of Islamic teachings within the oral tradition of Sinandong in Tanjungbalai. The study is motivated by the fact that Sinandong has generally been understood as a form of community entertainment, while the religious dimensions embedded in Malay culture have not yet been studied in depth. The study employs a qualitative field approach using observation, interviews, and documentation of Sinandong artists and the Malay community in Tanjungbalai City. The findings reveal that the Sinandong tradition developed under the influence of the Malay Sultanate and the role of ulama, who established Islam as the primary identity of the Malay community. In the social life of the Tanjungbalai community, Islam serves as a guide for thinking, behavior, and culture. Through its distinctive poetry, language, and rhythm, Sinandong conveys the values of tawakal (trust in God), ikhtiar (effort), obedience, patience, gratitude, and ethical living. This tradition also serves as a medium for entertainment, Islamic preaching, and education in instilling moral values, faith, and the habit of worship from an early age. This study confirms that Sinandong serves as a medium for the transmission of Islamic teachings that remains alive and continues to evolve within the Malay community of Tanjungbalai. The existence of this tradition demonstrates that local culture and Islamic values can coexist harmoniously and serve as a means of preserving Malay cultural identity for the younger generation amidst social change.